MUSICAL ACTIVITY IS A NECESSARY PROFESSIONAL QUALITY OF FUTURE MUSIC TEACHERS - Pashchenko, M.; Polianchuk, M. (SWorld-Ger Conference proceedings, 2024)
The definition of the concept of musical activity of an individual by scientists is considered. The main orientation of students' hearing is determined. The peculiarities of the formation of students' musical activity, which contributes to a differentiate